Preliminary results of the Getahovit-2 Cave excavations in 2018 - Irena, Kalantaryan; Ghanem, Ghanem (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
Except for the newly discovered archaeological sites that can be determined as classical models (keys), additional, deeper, information and examination in the study of the Chalcolithic period of Armenia can be found in the caves, rock shelters and open-air camps. In that list, Getahovit-2 cave has its own niche, in terms of the environmental context and its being very well stratified and dated due to systematic excavations. Moreover, the cave is the perfect example of a place that was used by pastoralist groups as a sheep and goat keeping place during the Chalcolithic period in the region and the first, where the phenomenon has been fixed and studies as well. The cave is located in the valley (N 40°54’38.5’’, E 045°05’59.7’’) formed by the Khachaghbyur River (the tributary of Aghstev River) at an elevation of c. 968 m.a.s.l., between the modern villages of Yenokavan and Getahovit (Tavush region). It consists of two halls: the first, opening to the south, covering an area of 64 m2, and the second accessed through a narrow passageway. The excavations, conducted by the Armenian-French joint project, began there in 2011 and continued until 2017. The results yielded cultural deposits nearly 2 m deep, with Medieval horizons, overlaying the Chalcolithic period. Finally, the Upper Palaeolithic horizon has been fixed by deep test sounding. With its radiocarbon dates, the Chalcolithic period attested from Getahovit-2 cave is placed very well in the middle sequence of the chronological chart based on radiometric dating. Additionally, one result showed very early Chalcolithic period presence (5289-4995 cal BC), which is extremely interesting. This contribution presents the preliminary results of the 2018 excavations undertaken by the Institute of Archaeology and Ethnography, NAS RA, with the financial support of the Ijevan Wine-Brandy Factory. Although only the preliminary results will be presented, some important particularities will be stressed in terms of the typological and technological differences of the pottery in comparison with the previous collections found in the cave. The discussion will concern the general situation and description of the newly excavated Chalcolithic layers after they were covered by mud streams mixed with small stones flowing into the hall. Some questions of stratigraphy will be presented which could be correlated with previous seasons’ excavations.